INDIGENIZATION OF ISLAMIC NUSANTARA EDUCATION (Case Study on the Nahdlatul 'Ulama Regional Representative Council of West Java) - Taja, Nadri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
This paper discusses the values of Islamic Nusantara Education which is considered to be one of the solutions to the various problems related to the fanaticism of groups that occurred in Indonesia. The purpose of this study is to describe the values of Islamic Education developed by the Nahdlatul 'Ulama Regional Representative Council of West Java, which can be used as one source of Islamic values in education. This is done because the Nahdlatul 'Ulama is one of the biggest majority group in Indonesia which still preserves the cultural values which are then internalized to the public. The method used in this study is a qualitative case study. From the research conducted, it was found that there are four things considered as the adopted, maintained, and inherited pedagogical value among members of the Nahdlatul 'Ulama Regional Representatives Council of West Java, which can be used as values in Islamic education – tolerant (tasamuh), balance (tawazun), moderate (tawasuth), and mutual assistance (ta'awaun).